Unambiguous Determination of Protein Arginine Ionization States in Solution by NMR Spectroscopy. Issue 1 (29th November 2016) - Yoshimura, Yuichi; Oktaviani, Nur Alia; Yonezawa, Kento; Kamikubo, Hironari; Mulder, Frans A. A.
Abstract: Because arginine residues in proteins are expected to be in their protonated form almost without exception, reports demonstrating that a protein arginine residue is charge‐neutral are rare and potentially controversial. Herein, we present a 13 C‐detected NMR experiment for probing individual arginine residues in proteins notwithstanding the presence of chemical and conformational exchange effects. In the experiment, the 15 N η and 15 N ϵ chemical shifts of an arginine head group are correlated with that of the directly attached 13 C ζ . In the resulting spectrum, the number of protons in the arginine head group can be obtained directly from the 15 N– 1 H scalar coupling splitting pattern. We applied this method to unambiguously determine the ionization state of the R52 side chain in the photoactive yellow protein from Halorhodospira halophila . Although only three H η atoms were previously identified by neutron crystallography, we show that R52 is predominantly protonated in solution. Abstract : Count the number of protons : An NMR experiment is presented for the direct counting of the number of protons in the arginine head group. This method allows the unambiguous determination of the charge state of arginine side chains, which was demonstrated on the arginine residue in the active center of photoactive yellow protein.